Motherhood, mental illness and recovery : stories of hope - Barber, Mary E.; Benders-Hadi, Nikole (Springer International Publishing, 2014)
Despite the importance of regaining social roles during recovery from mental illness, the intersection between motherhood and serious mental illness is often overlooked. This book aims to rectify that neglect. A series of introductory chapters describing current research and services available to mothers with serious mental illness are followed by personal accounts of clients reflecting on their parenting experiences. One goal of the book is to provide clinicians with information on this seldom addressed topic, which they can then use to help patients who are struggling with questions and barriers in their attempts to parent. The inclusion of personal accounts of mothers on issues such as stigma, fears, and discrimination in the context of parenting with a mental illness is intended to promote the message of mental illness recovery to a larger audience as well. Finally, it is hoped that this handbook will help inspire more research on mothers with mental illness and the creation of more services tailored to their needs.